Fatty acid profile, carcass traits and meat quality of Nellore steers following supplementation with various lipid sources - Carvalho, Isabela P. C. [UNESP]; Fiorentini, Giovani [UNESP]; Lage, Josiane F. [UNESP]; Messana, Juliana D. [UNESP]; Canesin, Roberta C. [UNESP]; Rossi, Luis G. [UNESP]; Reis, Ricardo A. [UNESP]; Berchielli, Telma T. [UNESP] (CSIRO Publishing, 2017)
The aim of the present study was to evaluate the fatty acid composition of meat and subcutaneous fat, carcass traits and meat quality of Nellore steers fed diets supplemented with various lipid sources. Forty-five young bulls, with average bodyweight of 441 ± 30 kg, were allotted into 10 paddocks, with five treatments, each consisting of two paddocks. The bulls were randomly assigned into one of the following five treatments, which consisted of four lipid sources: palm oil (PO), linseed oil, rumen protected fat (soybean-based oil), whole soybean, and a control (without additional fat). Trial duration was 120 days, which included 30 days of adaptation. Supplements were offered daily at 10 g/kg bodyweight per day. Dietary supplements for providing additional fat were formulated to consist of 10% ether extract. Lipid sources did not significantly affect the average daily gain (P ≤ 0.797) or dressing percentage (P ≤ 0.663). Supplementation with PO increased the concentrations of lauric acid (P ≤ 0.036) and myristic acid (P < 0.001) in the muscle and subcutaneous fat. Animals supplemented with linseed oil had significantly higher concentrations of conjugated linolenic acid in the meat (P ≤ 0.036) and fat (P ≤ 0.049) than did control animals. In the present study, the use of various lipid sources in dietary supplements of grazing cattle during finishing period did not affect carcass traits or physical attributes of beef. This absence of statistical significance may be related to the minimum number of repeat paddocks (2) per treatment. Thus, differences that can have a practical significance were not evidenced by statistical analysis. The inclusion of PO and protected fatty acids derived from soybean oil (rumen-protected fat) is not recommended as a method to improve the lipid profile of meat and subcutaneous fat of Nellore cattle.
Keywords: Brachiaria brizantha; conjugated linolenic acid; linseed oil; palm oil; rumen-protected fat.